Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity - Turcot, Valerie; Lu, Yingchang; Highland, Heather M.; Schurmann, Claudia; Justice, Anne E.; Fine, Rebecca S.; Loos, Ruth J. F. (Nature Publishing Group, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are similar to 10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed similar to 7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Genome-Wide Association; Melanocortin-4 Receptor Gene; Donepezil 23 Mg; Frameshift Mutation; Glucose-Homeostasis; Hypothalamic Ampk; Coding Variants; Blood-Pressure; Rare; Loci